2018
DOI: 10.1186/s12951-018-0428-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of atomic force microscopy in cancer research

Abstract: Atomic force microscopy (AFM) allows for nanometer-scale investigation of cells and molecules. Recent advances have enabled its application in cancer research and diagnosis. The physicochemical properties of live cells undergo changes when their physiological conditions are altered. These physicochemical properties can therefore reflect complex physiological processes occurring in cells. When cells are in the process of carcinogenesis and stimulated by external stimuli, their morphology, elasticity, and adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
125
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 160 publications
(133 citation statements)
references
References 172 publications
(147 reference statements)
4
125
0
4
Order By: Relevance
“…Studies have suggested that patients with the BRAF V600E mutation should be overtreated to some extent [47], because BRAF mutations are an independent risk factor for lymph node metastasis and are closely related to tumor size and invasiveness [48][49][50][51][52][53][54][55][56][57]. Both the clinical studies and the basic medical studies performed here suggest that the presence of the BRAF mutation may lead to a decrease in the efficacy of iodine-131 treatment.…”
Section: Discussionmentioning
confidence: 72%
“…Studies have suggested that patients with the BRAF V600E mutation should be overtreated to some extent [47], because BRAF mutations are an independent risk factor for lymph node metastasis and are closely related to tumor size and invasiveness [48][49][50][51][52][53][54][55][56][57]. Both the clinical studies and the basic medical studies performed here suggest that the presence of the BRAF mutation may lead to a decrease in the efficacy of iodine-131 treatment.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, the malignant progression and high mortality rates associated with these tumors are related to their insidious onset, frequent metastasis and recurrence, and poor prognosis . Treatment on the basis of early diagnosis is still the main approach for achieving long‐term cancer‐free survival . Although many biomarkers of malignant tumors are currently used in the clinical setting, all of these biomarkers have limitations.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Treatment on the basis of early diagnosis is still the main approach for achieving long-term cancer-free survival. [32][33][34][35][36] Although many biomarkers of malignant tumors are currently used in the clinical setting, all of these biomarkers have limitations. Therefore, many studies have focused on identifying more effective biomarkers to improve the early diagnosis of ma- 55 Moreover, hsa_circ_0033155 could serve as a biomarker or therapeutic target in non-small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid biopsy is currently an effective and non-invasive method. Some serum markers, such as Epstein Barr virus DNA and microRNA (miRNA), lactate dehydrogenase, and antigens have been recognized fortheir clinical value [4][5][6][7][8][9][10][11]. However, they also have some limitations.…”
Section: Introductionmentioning
confidence: 99%